Cascade applications of robust MIL-96 metal organic frameworks in environmental remediation: Proof of concept - Azhar, M.; Abid, H.; Tade, Moses; Periasamy, V.; Sun, Hongqi; Wang, Shaobin (Elsevier BV, 2018)
In this paper, we demonstrate a cascade application of functional materials in adsorption and catalysis. Metal organic frameworks, MIL-96, were synthesized by a single solvent (water), and methanol (MIL-96-Me) or ethanol (MIL-96-Et) modulated method. Methanol modulation results in a change in porous structure and better CO 2 adsorption and selectivity. After gas-phase adsorption of CO 2 , the MIL-96 can be reused for liquid-phase removal of water contaminants, demonstrating high capacities of para-hydroxybenzoic acid (p-HBA). Then, a transformation of the used MIL-96 by pyrolysis was employed to produce a metal oxide/C composite for catalytic activation of peroxymonosulfate (PMS) to degrade an organic pollutant, methyl orange. The composite exhibited excellent performance in the dye degradation. This study presents a proof of concept of integrated utilization of robust and functional nanomaterials for multiple applications without producing solid wastes after each use.